HUBUNGAN TINGKAT KEMAMPUANACTIVITIES OF DAILY LIVING(ADL) TERHADAP DISFUNGSI SOSIAL PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA PARE KABUPATEN KEDIRI - Yektiningsih, Erwin (Jurnal AKP, 2010)
Improving healthy service has given the influence to decrease the death rate of baby and child, increasing thelive  of  age  expectation,  the  last  number  of  old  persons  in  society  to  be  increase.  Increase  the  number  of  oldpersons  can  create  manyhealthy  of  old  persons  status  problem  because  of  decreasing  physiologic  function  ofmany body organ. The purpose of the research to examine the correlation of ADL ability with social disfunctionto  the  old  persons    and want  to  know the kind of social  disfunctional that  determinant in the  old  persons. Theresearch design use cross sectional approach by population of old persons at Tresna Werdha Social InstitutionPare-Kediri.  Fourthy  old  persons  has  been  got  as  sample  by  simple  random  sampling  technique.  There  isrelation correlation that significant between ADL ability level with social disfungtion (Pearson correlation testr =  0,465, p=  0,003), to know  the  assosiation  between ADL  ability level with social  disfungtion  kind will  beusedMann-Whitney  testwhich  be  gotten  result  statistically  un  association  between ADL  ability  level  with lowself esteem (p= 0,468) and interpersonal system (p= 0,618). Whereas to the association of ADL ability levelwith the kind of social disfunction performance system statistically show there are significant correlation (p =0,028). From the result can be concluded that there is relation correlation between ADL ability level and socialdisfunction, while ADL ability level with kinerja system there association. Based on thefounded of this researchsuggested  in  give  nursing  care  comprehensively  to  older  person  is  needed  holistic  approach  to  help  adaptionneed to changing of psychologic, social, and spiritual by increasing the ability and potent of the elderly  that stillbehad to adapt the change according to the ability